Greece: Back on track? - Klaus Schrader; David Benček; Claus-Friedrich Laaser (Kiel Institute for the World Economy (IfW), 2013)
At the turn of the year 2012/2013 the Eurogroup and the European Commission heralded the message that the worst crisis in Greece would be over. According to this message, the Greek government had delivered the promised steps of structural and fiscal reforms and had agreed with a tough timetable for further reforms. The slowdown of negative growth, the falling current account deficit, the reduction of the primary deficit and the various reform laws adopted by the Greek parliament were highlighted as evidence for a positive development in Greece (EU-Commission 2013a: 56). However, an in-depth analysis of Greece's economic development and potentials does not corroborate the image of a country that rises like a phoenix from the ashes (Figure 1). The economic downswing has continued in 2013 whereby it only slightly decelerated - real GDP will contract for the fifth consecutive year, probably by more than 4 %. Even the forecast of a slight growth by 0.6 % in 2014 rests on very optimistic assumptions on the reduction of unit labor costs, the successful liberalization of markets, the stabilization of the commercial banking system and the creation of a business environment convenient for attracting foreign direct investment. Looking at Greece's labor market the impression prevails that not even a faint light can be seen at the end of the tunnel: Mass unemployment will remain at a rate of 25 %, and youth unemployment at the 60 % threshold further exacerbates the labor market crisis. Rising unemployment results from lay-offs in the private sector while the public service and stateowned enterprises have mostly been spared from employment reductions so far. At least the cuts of public service salaries indicate empty treasuries and the austerity policy forced by the international financiers.
Keywords: 330